2022
DOI: 10.3390/cancers14051335
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Epigenomic Landscape of Juvenile Myelomonocytic Leukemia

Abstract: Juvenile myelomonocytic leukemia (JMML) is a rare myelodysplastic/myeloproliferative neoplasm of early childhood. Most of JMML patients experience an aggressive clinical course of the disease and require hematopoietic stem cell transplantation, which is currently the only curative treatment. JMML is characterized by RAS signaling hyperactivation, which is mainly driven by mutations in one of five genes of the RAS pathway, including PTPN11, KRAS, NRAS, NF1, and CBL. These driving mutations define different dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…In other myeloid malignancies, mutations in SWI/SNF genes seem to be extremely rare (< 1%), and, if present, they mostly affect ARID1A . This is the case for AML [ 51 ], CML [ 203 ], and myeloproliferative neoplasms such as juvenile myelomonocytic leukemia [ 204 , 205 ], chronic myelomonocytic leukemia [ 206 ], chronic neutrophilic leukemia [ 207 ], chronic eosinophilic leukemia [ 208 ], and others [ 112 , 209 213 ]. However, there are notable exceptions.…”
Section: Genetic Alterations Of Swi/snf Subunits In Hematological Mal...mentioning
confidence: 99%
“…In other myeloid malignancies, mutations in SWI/SNF genes seem to be extremely rare (< 1%), and, if present, they mostly affect ARID1A . This is the case for AML [ 51 ], CML [ 203 ], and myeloproliferative neoplasms such as juvenile myelomonocytic leukemia [ 204 , 205 ], chronic myelomonocytic leukemia [ 206 ], chronic neutrophilic leukemia [ 207 ], chronic eosinophilic leukemia [ 208 ], and others [ 112 , 209 213 ]. However, there are notable exceptions.…”
Section: Genetic Alterations Of Swi/snf Subunits In Hematological Mal...mentioning
confidence: 99%
“…Certain mutations in RAS pathway genes increase their activity, conferring a gain of function. NRAS and KRAS mutations cluster in the G12, G13, and Q61 residues, locking RAS in an active, GTP-bound state 4,5 . NF1 and CBL are tumor suppressing genes in which germline mutations occur in the context of neurofibromatosis type 1 and CBL syndrome, respectively, leading to enhanced RAS signaling 6…”
mentioning
confidence: 99%
“…7 Hypermethylation has been associated with poor clinical outcome in JMML. 5 Approximately 7% of patients with JMML have been reported to have mutations in SH2B3, 7 a gene which encodes the tumor suppressor LNK that negatively regulates JAK/STAT signaling. Previous studies have demonstrated that patients with JMML have increased STAT5 phosphorylation.…”
mentioning
confidence: 99%
See 2 more Smart Citations